Analysis of Students' Mastery of Concepts in Newton's Second Law Material Through the Rasch Model - Boby Syefrinando; Fauzan Sulman (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
The research aims to see students' conceptual understanding of Newton's second law material through the Rasch model. This research was conducted on physics education students at the Sulthan Thaha Saifuddin Jambi State Islamic University, totalling 29 active students in August 2023. The research method used was a qualitative descriptive research method regarding the procedures for organizing and carrying out observations, where the researcher did not carry out special treatment. to make changes to students, but looking at the real conditions that students have in modern conditions. The instrument consists of 45 items related to force and motion. Selection of questions to obtain appropriate questions using the Winsteps 3.65.0 program. The results of the analysis using the Rasch Model showed 23 fit items. The results of the analysis show that concept ability is very low, students' concept mastery is low where in percentage terms 97% have low concept mastery, and only 3% have moderate concept mastery ability, especially in Law II material.